Free online citation generators: which should undergraduates use with confidence? / Ho Chui Chui - Ho, Chui Chui (UiTM Cawangan Kedah, 2022)
With the introduction of research management software, most academic libraries recommend programs such as EndNote or Mendeley but undergraduates may not want to use these products if they need to document only a limited number of sources. In such cases, they may take advantage of the numerous free online citation generators such as Citation Machine, EasyBib and CiteFast. However, these programs are not always accurate. Therefore, students who are unfamiliar with the referencing style required by their course may be unable to detect errors in the generated references. This paper reports the author's search for a free, reliable and easy-to-use citation generator to recommend to her first-year undergraduate students. Three free citation builders, ZoteroBib, CiteMaker and Cite This For Me, were evaluated using actual sources used by students. It was found that the most frequent problem for all three programs was formatting citations such as capitalisation, punctuation and indentation. Although results showed that ZoteroBib outperformed the other two, it was still not perfect. Thus, it is imperative to remind students to check the generated citations carefully and correct any errors. The availability of citation generators certainly does not replace the necessity of learning to prepare citations manually.